2016
DOI: 10.1007/s13594-015-0274-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of glycerol monostearate and Tween 80 on the physical properties and stability of recombined low-fat dairy cream

Abstract: Recombined low-fat dairy cream (RLFDC) primarily comprises anhydrous milk fat and milk protein. The primary advantage of RLFDC is that its ingredients can be easily stored and transported, whereas its most notable disadvantage is poor stability. The effects of glycerol monostearate (GMS) or sorbitan monooleate ethoxylate (Tween 80) on the physical properties and stability of RLFDC (20% fat and 2% protein) were investigated in this study. Physical properties were evaluated according to droplet size, surface pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…This increase is brought on by the oleic acid molecules’ free carboxylic groups, which have negative charges [ 39 ]. The amphiphilic nature of these glycerides, which tend to be adsorbed onto the LCN surfaces, displaying a shielding effect, was also linked to the decreased ZP values of Captex 8000 and Capmul MCM [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…This increase is brought on by the oleic acid molecules’ free carboxylic groups, which have negative charges [ 39 ]. The amphiphilic nature of these glycerides, which tend to be adsorbed onto the LCN surfaces, displaying a shielding effect, was also linked to the decreased ZP values of Captex 8000 and Capmul MCM [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Hence, it can be assumed that glycerin can provide better stability and improve the physical properties of OEO-NCs. It has been reported that the emulsion stability and wettability of the particles are strongly dependent on the pH [ 31 ] and that increasing the pH of the emulsion causes higher absolute values of the Z-Pot, resulting in higher stability.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is important to notice that this rule applies only to an electrostatically stabilized system (27) . A reduction in ZP value was observed when the oleic acid ratio was increased above (10% w/w) which is associated with increased in particle size leading to reduction in surface charge density on the formed nanoparticles (28) .…”
Section: Particle Size and Zeta Potential Analysismentioning
confidence: 97%